2010
DOI: 10.1016/j.cub.2010.10.046
|View full text |Cite
|
Sign up to set email alerts
|

Disrupting Parietal Function Prolongs Dominance Durations in Binocular Rivalry

Abstract: Human brain imaging studies of bistable perceptual phenomena revealed that frontal and parietal areas are activated during perceptual switches between the two conflicting percepts. However, these studies do not provide information about causality, i.e., whether activity reports a consequence or a cause of the perceptual change. Here we used functional magnetic resonance imaging to individually localize four parietal regions involved in perceptual switches during binocular rivalry in 15 subjects and subsequentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
120
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(158 citation statements)
references
References 37 publications
16
120
3
Order By: Relevance
“…6) is consistent with earlier neuroimaging (7-9), electrophysiological (11), TMS (13)(14)(15), and neuropsychological (16)(17)(18) findings suggesting that frontoparietal regions might initiate perceptual switching. To the extent that the attentional load might be larger during perceptual switching than maintenance, these results are also consistent with previous GC results on visual spatial attention (34).…”
Section: Top-down Vs Bottom-up Influences During Perceptual Switchinsupporting
confidence: 80%
See 1 more Smart Citation
“…6) is consistent with earlier neuroimaging (7-9), electrophysiological (11), TMS (13)(14)(15), and neuropsychological (16)(17)(18) findings suggesting that frontoparietal regions might initiate perceptual switching. To the extent that the attentional load might be larger during perceptual switching than maintenance, these results are also consistent with previous GC results on visual spatial attention (34).…”
Section: Top-down Vs Bottom-up Influences During Perceptual Switchinsupporting
confidence: 80%
“…Firstly, frontal and parietal brain regions seem to be involved in perceptual switching, as demonstrated by neuroimaging (7-11) (but see ref. 12) as well as transcranial magnetic stimulation (TMS) (13)(14)(15) and lesion (16)(17)(18) studies. Secondly, functional MRI (fMRI) activity patterns in visual regions, including the primary visual cortex (V1) and lateral geniculate nucleus (LGN), correlate with the content of fluctuating percepts, as reflected in both activity fluctuations of an entire brain region (19)(20)(21)(22)(23)(24) and the fine spatial patterns of activity within a region (25)(26)(27).…”
mentioning
confidence: 99%
“…These picture sets also provide a valid contribution to a better understanding of the neural correlates of perceptual rivalry using ambiguous or bistable figures, such as Rubin's face/vase, the duck/rabbit picture, or the Necker cube (Bonneh, Pavlovskaya, Ring, & Soroker, 2004;Britz et al 2009;Kleinschmidt et al 1998;Long & Toppino, 2004;Lumer et al 1998;Zaretskaya et al 2010). In contrast to ambiguous figures that continuously, spontaneously, and unpredictably alternate between two mutually exclusive interpretations, our picture sets provide more control as to when the switch occurs.…”
Section: Discussionmentioning
confidence: 98%
“…These stimuli have been used to explore numerous perceptual phenomena, including binocular rivalry (Blake & Logothetis, 2002;Meng & Tong, 2004), the influence of cues on perception (Panichello, Cheung, & Bar, 2013, for an overview), the ability of children to switch between the two interpretations (Doherty & Wimmer, 2005;Gopnik & Rosati, 2001; M.C. Wimmer & Doherty, 2011), the brain areas associated with perceptual switches (Britz, Landis, & Michel, 2009;Kleinschmidt et al 1998;Lumer, Friston, & Rees, 1998;Zaretskaya, Thielscher, Logothetis, & Bartels, 2010), and perceptual hysteresis (Hock et al, 1993). Similarly, studies using picture sets that morph from one unique object (e.g., a rabbit) to another (e.g., a duck), with various levels of ambiguity in between, have shown that pictures are perceived categorically (i.e., as either a duck or a rabbit, but not as an alternate, third object representing the gradual merging of both; Hartendorp et al 2010;Newell & Bülthoff, 2002;Verstijnen & Wagemans, 2004).…”
mentioning
confidence: 99%
“…Causally manipulating neural activity in these regions using transcranial magnetic stimulation (TMS) with continuous theta-burst stimulation decreases switch rate (Kanai et al 2010) showing that these areas play a causal role in generating perceptual switches. Moreover, applying TMS to a slightly more anterior part of parietal cortex has the opposite effect on switch rates in binocular rivalry (Carmel et al 2010;Zaretskaya et al 2010). Taken together this suggest a sophisticated model in with parietal (and perhaps prefrontal) cortices play a complex causal role in generating top-down signals that ultimately resolve perceptual competition in ventral visual cortex (Kanai et al 2011).…”
Section: Access To Consciousnessmentioning
confidence: 87%